miR-10b-5p promotes tumor growth by regulating cell metabolism in liver cancer via targeting SLC38A2 - Mingzhi Xia; Jie Chen; Yingyun Hu; Bin Qu; Qianqian Bu; Haoming Shen (Cancer Biology & Therapy)
Metabolic reprogramming plays a critical role in hepatocarcinogenesis. However, the mechanisms regulating metabolic reprogramming in primary liver cancer (PLC) are unknown. Differentially expressed miRNAs between PLC and normal tissues were identified using bioinformatic analysis. RT-qPCR was used to determine miR-10b-5p and SCL38A2 expression levels. IHC, WB, and TUNEL assays were used to assess the proliferation and apoptosis of the tissues. The proliferation, migration, invasion, and apoptosis of PLC cells were determined using the CCK-8 assay, Transwell assay, and flow cytometry. The interaction between miR-10b-5p and SLC38A2 was determined using dual-luciferase reporter assay. A PLC xenograft model in BALB/c nude mice was established, and tumorigenicity and SLC38A2 expression were estimated. Finally, liquid chromatography – mass spectrometry (LC-MS) untargeted metabolomics was used to analyze the metabolic profiles of xenograft PLC tissues in nude mice. miR-10b-5p was a key molecule in the regulation of PLC. Compared with para-carcinoma tissues, miR-10b-5p expression was increased in tumor tissues. miR-10b-5p facilitated proliferation, migration, and invasion of PLC cells. Mechanistically, miR-10b-5p targeted SLC38A2 to promote PLC tumor growth. Additionally, miR-10b-5p altered the metabolic features of PLC in vivo. Overexpression of miR-10b-5p resulted in remarkably higher amounts of lumichrome, folic acid, octanoylcarnitine, and Beta-Nicotinamide adenine dinucleotide, but lower levels of 2-methylpropanal, glycyl-leucine, and 2-hydroxycaproic acid. miR-10b-5p facilitates the metabolic reprogramming of PLC by targeting SLC38A2, which ultimately boosts the proliferation, migration, and invasion of PLC cells. Therefore, miR-10b-5p and SLC38A2 are potential targets for PLC diagnosis and treatment.